PEMBENTUKAN MODAL UNTUK PENGEMBANGAN USAHA PENANGKAPAN IKAN OLEH NELAYAN KELURAHAN MANADO TUA SATU KECAMATAN BUNAKEN KOTA MANADO - Pontoh, Otniel (AKULTURASI, 2015)
Abstract The aim of this study is to examine the formation of capital for the development of fishing effort by fishermen in the village I District of Manado Tua Bunaken Manado City. The method applied in this study is explorative case study. Sampling using simple random sample withdrawal. Data collected by means of active participation, interviews, and filling the list of questions (questionnaire). Qualitative analysis by making the description of the object of study while quantitative analysis reached by statistical calculation and simple math. The results showed that the housing situation of fishermen considered to be adequate, level of education is still low. In terms of venture capital, Manado Tua fishermen no avail loan from the bank, they are reluctant to use and does not want to take the risk because the business is financed by loans require collateral in the form of credit financed businesses as well as the wealth of clients. Fishing effort contained in the island of Manado Tua is still using its own capital and less attention from the government. If no help is given sometimes incomplete, the size of the nets is not complete and the boat does not correspond guidelines also not equipped with a motor. Should the government through the Department of Fisheries to provide credit facilities with low interest and as well as providing information about fisheries economics. Keyword: Capital, Business development, ishing, fishermen, Village Manado Tua I